Aktivitas Jamaah Majelis Taklim As-Syifa Walmahmudiyah Desa Sayati dalam Studi Interaksionisme Simbolik - Mamay Siti Maryam (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2021)
The purpose of this article is to examine the activities of the Jamaah Majelis Taklim As-Syifa Walmahmudiyyah in Sayati Village in the study of symbolic interactionism. Using the paradigm of Interpretivism in the approach of symbolic interactionism theory refers to, George Herbet Mead. This research is within the discipline of qualitative research. The focus in this research is how to interpret mind-concept (Mind) self-concept and social interaction (Society) of Jamaah Majelis Taklim As-Syifa Walmahmudiyah. The results showed that the recitation activity was a proselytizing activity that was beneficial for the thoughts, self, and social life of the congregation. Activities that have become a tradition of the As-Syifa Walmahmudiyah recitation congregational taklim assembly are recitation activities that have a unique character. The recitation activities held were unusual, namely the time for the recitation from ba'da Isya at 20.00 until dawn. The implementation of the recitation has become a positive habit for the congregation and the surrounding community. The effectiveness of the recitation has a positive and negative impact on the performance of the As-Syifa Walmahmudiyyah majelis taklim congregation